THE CORRELATION BETWEEN RELIGIOSITY AND SELF-EFFICACY IN PATIENTS WITH CORONARY ARTERY DISEASE - Wantiyah Wantiyah; Firda Romadhonia Putri Rivani; Mulia Hakam (Belitung Raya Foundation, Indonesia, 2020)
Background: In managing life with coronary artery disease, having self-efficacy is considered important. Self-efficacy reduces risk factors for coronary artery disease by encouraging the self-control process. The involvement of religiosity aspects can be a motivation to increase self-efficacy in maintaining an individual’s health status. Objective: This study aimed to examine the correlation between religiosity and self-efficacy in patients with coronary artery disease. Methods: This was a correlational study with a cross-sectional approach involving 112 respondents selected using an accidental sampling method in a hospital at Jember District, East Java, Indonesia. Data were collected from December 2019 to January 2020 using the Religiosity Scale and Cardiac Self-Efficacy (CSE). The Spearman’s rank test was used to analyze data. Results: The results showed that the respondents’ religiosity had a median value of 3.84 (min-max: 3.00-4.00), while the median value of self-efficacy was 3.60 (min-max: 2.90-4.00). There was a significant correlation between religiosity and self-efficacy (p = <0.001, r = 0.540, α = 0.05). Conclusion: The moderate positive correlation between religiosity and self-efficacy indicated that the higher value of religiosity leads to a higher value of self-efficacy. The religious value through rituals of prayer or meditation could increase the self-efficacy of patients with coronary artery disease. Nurses are recommended to maintain the religiosity of patients at a good level to improve their self-efficacy and maintain the optimal health status.